15(8c-1)-8=118c+15

Simple and best practice solution for 15(8c-1)-8=118c+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(8c-1)-8=118c+15 equation:


Simplifying
15(8c + -1) + -8 = 118c + 15

Reorder the terms:
15(-1 + 8c) + -8 = 118c + 15
(-1 * 15 + 8c * 15) + -8 = 118c + 15
(-15 + 120c) + -8 = 118c + 15

Reorder the terms:
-15 + -8 + 120c = 118c + 15

Combine like terms: -15 + -8 = -23
-23 + 120c = 118c + 15

Reorder the terms:
-23 + 120c = 15 + 118c

Solving
-23 + 120c = 15 + 118c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-118c' to each side of the equation.
-23 + 120c + -118c = 15 + 118c + -118c

Combine like terms: 120c + -118c = 2c
-23 + 2c = 15 + 118c + -118c

Combine like terms: 118c + -118c = 0
-23 + 2c = 15 + 0
-23 + 2c = 15

Add '23' to each side of the equation.
-23 + 23 + 2c = 15 + 23

Combine like terms: -23 + 23 = 0
0 + 2c = 15 + 23
2c = 15 + 23

Combine like terms: 15 + 23 = 38
2c = 38

Divide each side by '2'.
c = 19

Simplifying
c = 19

See similar equations:

| i^4-1=0 | | 2x+15=3x-10 | | -0.75-3x=-9 | | 11x+5x=18 | | 3t-14=78 | | 3+6x+6x=99 | | 5(2c-1)-3=5c+7 | | 6x+2+40=90 | | 3(2x-15)-4=55 | | 7y=27 | | 2t-6=3(t+6) | | -3x+12=-12 | | 5x+34=73 | | 90.50-77.75= | | 7x+8-2x=18 | | .7x+1=-3 | | 3(2x-15)=55 | | 21+x=25+2x | | 35x-3=214 | | 30-18=4(x-1) | | g=0.16(w+40) | | 30+275=1225 | | -4x-8=32 | | 5-.75x=-7 | | 10a-2=7a+1 | | 1x+-8=3(-2x+9) | | 50c-300=250 | | z^2-6X+7=2 | | 3x+24=63 | | 8k^4*2k= | | x^2-12=3 | | 2/3-7/4=5/12 |

Equations solver categories